Inhibition of IL-12 heterodimers impairs TLR9-mediated prevention of early mouse plasmacytoma cell growth - Mandour, Mohamed F.; Soe, Pyone Pyone; Castonguay, Anne-Sophie; Van Snick, Jacques; Coutelier, Jean-Paul (Frontiers in Medicine, 2023)
Natural prevention of cancer development depends on an efficient immunosurveillance that may be modulated by environmental factors, including infections. Innate lymphoid cytotoxic cells have been shown to play a major role in this immunosurveillance. Interleukin-12 (IL-12) has been suggested to be a key factor in the activation of innate cytotoxic cells after infection, leading to enhancement of cancer immunosurveillance. The aim of this work was to analyse in mouse experimental models by which mechanisms the interaction between infectious agent molecules and the early innate responses could enhance early inhibition of cancer growth and especially to assess the role of IL-12 by using novel antibodies specific for IL-12 heterodimers. Ligation of Toll-like Receptor (TLR)9 by CpG protected mice against plasmacytoma TEPC.1033.C2 cell early growth. This protection mediated by innate cytolytic cells, was strictly dependent on IL-12 and partly on gamma-interferon. Moreover the protective effect of CpG stimulation, and to a lesser extend of TLR3 and TLR7/8, and the role of IL-12 in this protection was confirmed in a model of early mesothelioma AB1 cell growth. These results suggest that modulation of the mouse immune microenvironment by ligation of innate receptors deeply modify the efficiency of cancer immunosurveillance through the secretion of IL-12, which may at least partly explain the inhibitory effect of previous infections on the prevalence of some cancers.